Transforming the global landscape - Bossio, Deborah A. (2014)
Rapid land transformation driven by large scale investments is one of the big trends defining this century. In a virtual briefing for the Global Donor Platform members CIAT agriculture expert Deborah Bossio dismisses the cry for more investments often heard in development circles. From her perspective a lack of investments is not the problem. The more pressing question is whether these large scale investments could be sustainable and socially inclusive. How are they going to play out in the end? Another emerging feature, according to Bossio, is the dominance of globalization as well as foreign income and international trade as major drivers of land use change. Taking a closer look at these dynamics shows that we aim at achieving multiple goals (sustaining communities, produce goods, store carbon, protect wildlife, sustain biodiversity, ecosystem services). The landscapes approach provides a vehicle for realizing those objectives. After outlining the reasons behind choosing landscapes approaches, Deborah rounds off with introducing specifics of CIAT’s landscapes approach. Deborah Bossio is the director of soils research area at CIAT. She is based in Nairobi, Kenya, and has more than 15 years experience working in sustainable agriculture development research. See the virtual briefing here: https://www.youtube.com/watch?v=T-sUzAC-B7w